Relation between Extent of Participation and Extent of Knowledge of Farm Women in Various Farms Practices - Mishra, R.; Gupta, A.K. (International Journal of Social Sciences and Management, 2017)
Agriculture is an important part of India's economy and at present it is among the top two farm producers in the word. This sector provides approximately present of the total number of jobs available in India and contributes around 13.5 percent to the GDP. Agriculture is the only means of living for almost two-thirds of the employed class in India. As being stated by the economic data of financial 2014-15, agriculture has acquired 13.5 percent of India's GDP. The agriculture sector of India has occupied almost 43 percent of India's geographical area agriculture play a vital role in the in the Indian economy over 70 percent of the rural house hold depend on agriculture. Agriculture is an important sector of Indian economy as it contributes about 60 percent job the population. the food grain protection has form 57 million tons (MT) in 1950-57 to268MT during 2013-14 highest ever since independence. In the years since its independence, India has made immense progress towards food security. Indian population has tripled, and food - grain production more than quadrupled. There has been a substantial increase in available food-grain per capita. Present study was carried out in two blocks of district Satna with 120 farm women. Eight farm practices were selected after the consultation with officials and farmwomen. Correlation coefficient was used to find out relation between extent of knowledge and extent of participation of the farmwomen with regard to the practices. It was found that there is a equal variables positive and negative, significance and non-significant relationship between participation and knowledge of the respondents. Int. J. Soc. Sc. Manage. Vol. 4, Issue-3: 198-201